Kajian Biaya Dampak Pembangunan Revitalisasi Kawasan Gedung Perundingan Linggarjati di Kecamatan Cilimus Kabupaten Kuningan - Muhammad Dzulfikar; Tonny Judiantono; Yulia Asyiawati (UNISBA Press, 2022)
Abstract. In 2016, the West Java Provincial Government has planned development activities for the Revitalization of the Linggarjati Negotiation Building Area, which is included in the Building and Environmental Management Plan for the Linggajati Village Cultural Heritage Tourism Area. The revitalization of the Linggarjati Negotiation Building Area is not only the revitalization of the Linggarjati Negotiation Building, but the revitalization activities consist of the development of tourism areas so as to have an impact on local government finances in meeting the level of service for public goods. The purpose of this study is to identify the predicted impact of local government financing in the revitalization of the Linggarjati Negotiation Building Area. The approach used to achieve the study objectives is a special procedure approach with the case study method analysis method. From the results of the study, it was found that the financing issued by the Regional Government was Rp. 205,857,496,234, for the fulfillment of infrastructure needs. Meanwhile, the income that is expected to be received by the regional government is Rp. 323,983,216,483 sourced from permits, taxes, and regional levies. Based on the analysis carried out, it can be concluded that the construction of the revitalization of the Linggarjati Negotiation Building Area is not expected to be a burden on the regional government's finances. The Regional Government of Kuningan Regency must prepare regulations related to the amount of retribution. Abstrak. Pada tahun 2016, Pemerintah Provinsi Jawa Barat telah merencanakan kegiatan pembangunan untuk Revitalisasi Kawasan Gedung Perundingan Linggarjati, yang termasuk kedalam Rencana Tata Bangunan dan Lingkungan Kawasan Wisata Cagar Budaya Kelurahan Linggajati. Revitalisasi Kawasan Gedung Perundingan Linggarjati tidak hanya revitalisasi Gedung Perundingan Linggarjati, tapi kegiatan revitalisasi tersebut terdiri dari pengembangan kawasan pariwisata sehingga menimbulkan dampak terhadap keuangan Pemerintah daerah dalam pemenuhan tingkat pelayanan terhadap barang public. Tujuan dari kajian ini adalah mengidentifikasi prediksi dampak pembiayaan Pemerintah Daerah dalam pembangunan revitalisasi Kawasan Gedung Perundingan Linggarjati. Pendekatan yang digunakan untuk mencapai tujuan studi adalah pendekatan prosedur khusus dengan metode analisis case study method. Dari hasil studi diperoleh bahwa pembiayaan yang dikeluarkan oleh Pemerintah Daerah sebesar Rp. 205.857.496.234, untuk pemenuhan kebutuhan infrastruktur Sedangkan pendapatan yang diperkirakan akan diterima Pemerintah daerah adalah sebesar Rp. 323.983.216.483 yang bersumber dari perizinan, perpajakan, dan retribusi daerah. Berdasarkan analisis yang dilakukan dapat disimpulkan bahwa pembangunan revitalisasi Kawasan Gedung Perundingan Linggarjati diperkirakan tidak akan membebani terhadap keuangan Pemerintah Daerah. Pemerintah Daerah Kabupaten Kuningan harus mempersiapkan aturan-aturan yang terkait dengan besaran retribusi.